Dielectric and ferroelectric properties of BST ceramics obtained by a hydrothermally assisted complex polymerization method. Issue 9 (November 2015) - Ćirković, Jovana; Vojisavljević, Katarina; Nikolić, Nenad; Vulić, Predrag; Branković, Zorica; Srećković, Tatjana; Branković, Goran
Abstract: Ba0.8 Sr0.2 TiO3 (BST) powder, obtained by a hydrothermal treatment of precursor solution previously prepared by a complex polymerization method (HT-CPM), was uniaxially pressed and sintered at 1280 °C for 1–32 h. The sintering effect on structural parameters, phase composition, dielectric and ferroelectric properties was investigated. Rietveld refinement analysis of BST ceramics showed that predominant phase was tetragonal BST with monoclinic Ba6 Ti17 O40 (B6T17) as a secondary phase. Phase contents determined by Rietveld refinement match well with the results of energy dispersive X-ray analysis. Dielectric and ferroelectric properties of BST ceramics have been correlated with density of sintered compacts, phase composition, structural parameters and microstructure. The sample sintered for 16 h showed the highest density (93% ρ t ), as well as the highest value of dielectric constant ( 2300) and remanent polarization – Pr (2 μC/cm 2 ) among investigated samples.